Innovative Polymeric Waste Management Systems to Enhance Circular Economy - Shinde, Prafulla (Digital Repository of Theses - SSBM Geneva, 2025)
The increasing difficulties presented by polymeric waste have emphasized the immediate requirement for inventive solutions that may tackle environmental issues while promoting economic viability. This research study explores polymeric waste management systems, specifically examining their ability to enhance the principles of the circular economy. The study wants to gain a full grasp of the latest breakthroughs in polymeric waste disposal technology by performing a rigorous literature analysis and examining case studies. The study evaluates the effectiveness of different methods, including mechanical reuse, chemical recycling, and developing waste-to-energy technologies, in both decreasing environmental harm and boosting resource effectiveness and economic resilience. The research aims to understand the complex factors influencing the acceptance and spread of new polymeric waste management technologies. It takes an interdisciplinary approach, combining environmental science, economics, engineering, and policy studies. The paper provides a clear analysis of the main difficulties and possibilities, offering practical advice to policymakers, business participants, and researchers to speed the goal of speeding up the shift toward an environmentally friendly and sustainable economy. To conduct a comprehensive statistical analysis, the study utilized established commercial statistical programs such as Excel and SPSS. Various statistical methodologies were considered for this study. However, the selected approaches included regression, analysis of variance (ANOVA), and mean, independent samples t-test, as well as standard deviation. The choice of methodology depended on the specific objectives and hypotheses of the research.